2010
DOI: 10.1101/gad.608210
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin organizes chromatin loops at DNA replication factories

Abstract: Genomic DNA is packed in chromatin fibers organized in higher-order structures within the interphase nucleus. One level of organization involves the formation of chromatin loops that may provide a favorable environment to processes such as DNA replication, transcription, and repair. However, little is known about the mechanistic basis of this structuration. Here we demonstrate that cohesin participates in the spatial organization of DNA replication factories in human cells. Cohesin is enriched at replication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
209
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(231 citation statements)
references
References 56 publications
21
209
1
Order By: Relevance
“…Our experiments with heterokaryon-mediated reprogramming support studies that have shown a role for cohesin in DNA replication (Terret et al 2009;Guillou et al 2010), and this emerging role is important for the activation of pluripotency gene expression by somatic cells in ES cell heterokaryons, where the depletion of cohesin results in slow S-phase progression and impaired pluripotency gene expression. This role is mechanistically distinct from chromosome segregation in mitosis (Nasmyth and Haering 2009;Terret et al 2009;Guillou et al 2010).…”
Section: Emerging Cohesin Functions In Dna Replicationsupporting
confidence: 61%
See 4 more Smart Citations
“…Our experiments with heterokaryon-mediated reprogramming support studies that have shown a role for cohesin in DNA replication (Terret et al 2009;Guillou et al 2010), and this emerging role is important for the activation of pluripotency gene expression by somatic cells in ES cell heterokaryons, where the depletion of cohesin results in slow S-phase progression and impaired pluripotency gene expression. This role is mechanistically distinct from chromosome segregation in mitosis (Nasmyth and Haering 2009;Terret et al 2009;Guillou et al 2010).…”
Section: Emerging Cohesin Functions In Dna Replicationsupporting
confidence: 61%
“…Cohesin and replication are intimately linked, since cohesion between sister chromatids is established during replication in S phase (Gerlich et al 2006;Nasmyth and Haering 2009;Terret et al 2009;Gause et al 2010). Cohesin associates with origins of DNA replication in Xenopus (Gillespie and Hirano 2004;Takahashi et al 2004), Drosophila (MacAlpine et al 2010, and mammalian genomes (Guillou et al 2010), where cohesin affects the spacing of replication origins in cohesin-depleted cells (Guillou et al 2010), the progression of replication forks (Terret et al 2009), and the restart of stalled forks (Tittel-Elmer et al 2012). As a result, altering the dosage or function of cohesin can affect DNA replication (Terret et al 2009;Guillou et al 2010;Tedeschi et al 2013).…”
Section: Cohesin Myc Dna Replication and Reprogrammingmentioning
confidence: 99%
See 3 more Smart Citations